2019
DOI: 10.15171/jhp.2019.47
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of curcumin on hippocampus dentate gyrus injury induced by nicotine in rats

Abstract: Introduction: Nicotine is the most important alkaloid compound in tobacco and is a major risk factor in the development of functional disorder of several organ systems. Some plants produce Curcumin, which has antioxidant and neuroprotective properties. This study was designed to evaluate the therapeutic effects of curcumin against nicotine injury on the hippocampus CA1 region of rats. Methods: In this study, 48 male Wistar rats were randomly assigned to eight groups: Normal control (saline) group, Nicotine con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Jalili et al investigated the therapeutic efficacy of curcumin against nicotine-induced injury in the hippocampus CA1 region of rats (Jalili et al, 2019). It has been shown that nicotine exposure significantly enhanced NO levels, and diminished total antioxidant capacity and neuronal dendritic spines and neuron numbers.…”
Section: Protective Effects Against Cs-induced Cognitive Impairment A...mentioning
confidence: 99%
“…Jalili et al investigated the therapeutic efficacy of curcumin against nicotine-induced injury in the hippocampus CA1 region of rats (Jalili et al, 2019). It has been shown that nicotine exposure significantly enhanced NO levels, and diminished total antioxidant capacity and neuronal dendritic spines and neuron numbers.…”
Section: Protective Effects Against Cs-induced Cognitive Impairment A...mentioning
confidence: 99%